2015
DOI: 10.1007/s10711-015-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian L-stability of Lagrangian translating solitons

Abstract: Abstract. In this paper, we compute the first and second variation formulas for the F-functional of translating solitons and study the Hamiltonian L-stability of Lagrangian translating solitons. We prove that any Lagrangian translating soliton is Hamiltonian L-stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The stability of soliton solutions to mean curvature flow under certain weighted volume functional was first studied by Colding-Minicozzi [7] for shrinking solitons in hypersurface case, and generalized to higher codimensional case by Andrews-Li-Wei [1], Arezzo-Sun [2], and Lee-Lue [16], but note that their functional ("entropy") is different from the f -volume functional. For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of soliton solutions to mean curvature flow under certain weighted volume functional was first studied by Colding-Minicozzi [7] for shrinking solitons in hypersurface case, and generalized to higher codimensional case by Andrews-Li-Wei [1], Arezzo-Sun [2], and Lee-Lue [16], but note that their functional ("entropy") is different from the f -volume functional. For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
“…For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
“…In this section, we will recall some results for the first variation and second variation formulas. Since the proofs can be found in Section 4 of [1] with f = T, x , where we dealt with more general cases (see also [14]), we omit the details here.…”
Section: Preliminariesmentioning
confidence: 99%
“…A translating soliton Σ n in C n is called a Lagrangian translating soliton if it is also a Lagrangian submanifold of C n . In [14], L. Yang proved that any Lagrangian translating soliton is Hamiltonian L-stable. In this paper, we prove that it is in fact Lagrangian L-stable: Theorem 1.1.…”
Section: Introductionmentioning
confidence: 99%